2020
DOI: 10.1038/s41467-019-14044-x
|View full text |Cite
|
Sign up to set email alerts
|

Trapped ion mobility spectrometry and PASEF enable in-depth lipidomics from minimal sample amounts

Abstract: A comprehensive characterization of the lipidome from limited starting material remains very challenging. Here we report a high-sensitivity lipidomics workflow based on nanoflow liquid chromatography and trapped ion mobility spectrometry (TIMS). Taking advantage of parallel accumulation-serial fragmentation (PASEF), we fragment on average 15 precursors in each of 100 ms TIMS scans, while maintaining the full mobility resolution of co-eluting isomers. The acquisition speed of over 100 Hz allows us to obtain MS/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
160
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(171 citation statements)
references
References 45 publications
4
160
0
1
Order By: Relevance
“…The 20 min LC‐gradient started with 40% solvent B and was increased in the following way: 2 min, 43%; 2.1 min, 50%; 12 min, 54%; 12.1 min, 70%; 18 min, 99%, 18.1 min, 40%, 20 min, 40% solvent B. The LC system was coupled to a timsTOF Pro instrument with ESI source (Bruker Daltonics, Bremen, Germany) essentially as described . Briefly, ions were detected in positive ion mode in the mass range of m/z 100–1300 using PASEF technology .…”
Section: Methodsmentioning
confidence: 99%
“…The 20 min LC‐gradient started with 40% solvent B and was increased in the following way: 2 min, 43%; 2.1 min, 50%; 12 min, 54%; 12.1 min, 70%; 18 min, 99%, 18.1 min, 40%, 20 min, 40% solvent B. The LC system was coupled to a timsTOF Pro instrument with ESI source (Bruker Daltonics, Bremen, Germany) essentially as described . Briefly, ions were detected in positive ion mode in the mass range of m/z 100–1300 using PASEF technology .…”
Section: Methodsmentioning
confidence: 99%
“…Our group and others developed machine-learning-based prediction (e.g., MetCCS 27,28 , LipidCCS 29 , DeepCCS 30 ) and quantum chemistry-based theoretical calculation (e.g., ISiCLE 31 ) approaches to generate large-scale CCS values for metabolites, lipids and other compounds. Coupling IM-MS with LC separation and data-independent or data-dependent MS/MS techniques (e.g., MS E , AIF, and PASEF) enables simultaneous acquisition of four-dimensional metabolomics data within one analysis, including MS1, RT, CCS, and MS/MS 32,33 . However, limited studies have integrated multi-dimensional properties in IM-MS towards the large-scale annotation of both known and unknown metabolite in untargeted metabolomics 11 .…”
mentioning
confidence: 99%
“…In MS/MS mode, this opens up the possibility to step the precursor selection window as a function of ion mobility, allowing the fragmentation of multiple precursors during a single TIMS scan 13 . We termed this novel scan mode parallel accumulation -serial fragmentation (PASEF) and demonstrated that it increases MS/MS rates more than ten-fold without any loss in sensitivity as is otherwise inherent to faster scanning rates 10,15 .…”
mentioning
confidence: 99%